CHALLENGES OF DISCRETE EVENT SIMULATION IN THE EARLY STAGES OF PRODUCTION SYSTEM DESIGN - Flores-García, Erik; Wiktorsson, Magnus; Bruch, Jessica; Jackson, Mats (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
This study analyzes the challenges of applying discrete event simulation in the early stages of production system design. Highlighting the implications of new production processes and technologies leading to improved competitiveness, this study provides novel contributions to the understanding of discrete event simulation based on three case studies of the transformation of legacy production systems in the heavy vehicle industry. The findings of this study show that equivocal or ambiguous understanding about new production processes or technologies, and uncertainty about necessary data input and the interrelation of subsystems in production, are critical in addressing discrete event simulation-related challenges. These findings highlight the need for an established process to manage assumptions and simplifications during the design, development, and deployment of discrete event simulation models as a countermeasure against uncertainties, improving manufacturing system design and practice.